Resistance : an indigenous response to neoliberalism - Bargh, Maria, 1977- (Huia, 2007)
This is a collection by New Zealand Maori academics, activists and leaders on resistance to neoliberalism. This unique book features a range of views that are often invisible to current debates on globalisation.